Marantic Endocarditis: A Rare Early Presentation Of Invasive Ductal Carcinoma Of The Breast - Butt, Madiha; Rafique, Zahra; Iftikhar, Fazeelat; Farooq; Rafique, Khadija; Adil, Muhammad (Journal of Rawalpindi Medical College, 2024)
Non-bacterial thrombotic endocarditis also known as Libman-sack endocarditis is a rare disease involving mostly mitral and aortic valves. It’s more commonly associated with malignancy than autoimmune disease. It can be diagnosed definitively postmortem and antepartum. It presents with signs and symptoms of arterial thromboembolism. Embolization is the most common symptom of marantic endocarditis. This can present as stroke, myocardial infarction, acute intestinal ischemia, pulmonary thromboembolism, splenic infarction, or transient ischemic attack. The pathophysiology involves the presence of sterile growths and fibrin deposits on heart valves. We present a case of a 35-year-old female who initially presented with the embolic complication of marantic endocarditis. She had an early diastolic murmur and a left arm weakness on her first presentation to the hospital. Further workup revealed vegetation on the aortic valve on echocardiography. Her blood culture as well as related tumor markers were negative. She developed a lump in her right breast after 1 month which on investigation turned out to be an invasive ductal carcinoma breast. Through this report, we highlight the importance of considering the workup for malignancy every time a patient comes with such symptoms. Keywords: Endocarditis, Ductal Carcinoma, Thromboembolism.